KUANTITASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT SERTA KONSENTRASI ASAM LAKTAT DARI FERMENTASI IKAN GABUS (Channa striata), IKAN NILA (Oreochromis niloticus), DAN IKAN SEPAT (Trichogaster trichopterus) PADA PEMBUATAN BEKASAM - Novianti, Dewi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
This  study  aims  to determine the quantitation of lactic acid bacteria and lactic acid bacteria as well as identify the concentration of lactic acid produced  from fermented catfish (Channa striata), tilapia (Oreochromis niloticus), and fish Sepat  (Trichogaster trichopterus) on maked bekasam (fish fermented). This  research  was conducted at the Center for Health Laboratory Palembang on July till August 2009 . Research  used  titrimetric  method  for determining  the  levels  of  lactic acid. Total  Plate  Count  method  to  determine  the  amount  of  lactic  acid forming bacteria, while  the  identification  of  lactic  acid  bacteria is done through biochemical  tests  and  test  the differential characteristics  of  lactic  acid   forming bacteria . The highest  content of lactic acid bacteria is 124.904 x 103 colonies/ml and the highest levels of lactic acid is 6.363% derived from Sepat fermented fish. Sepat fermented fish and tilapia on making bekasam found lactic acid bacteria of the genus Lactobacillus sp, Pediococcus sp  and Streptococcus sp. While the results of fermentation bekasam found only in fish cork lactic acid bacteria of the genus Lactobacillus and Streptococcus sp. Key words: fermentation, bekasam, identification, lactic acid bacteria,